DUSTY EXPLOITING of CHAFF PADDY UPON WHICH HARD MIXTURE TILE SOIL IN KARANG PENANG SAMPANG - Sudijono, Sudijono (WAKTU, 2011)
Chaff Paddy is external shares from paddy item. about/around 20 % from paddy wight is paddy chaff and more or less 15 % from composition lock up is lock up paddy which is always yielded is each time burned. ( Hara - 1986). Ash Lock up Paddy have pozolan element and contain silica. silica represent worthwhile chemicals and its application is very wide of strarting electronic area. mechanic. medical, building till other area. One of the silica serbuk exploiting is upon which ceramic making mixture of art ( hara. 1986). Dusty waste of this paddy chaff will be developed for the materials of bangunnan that is upon which mixture making of clay tile in Rock Penang Coat with lacquer so that can yield qualified Hat land;ground tile as according to SNI 03-2095-1998. Used by Mixture composition is heavy comparison 10 TL : 0 ASP ( control), 10 T : 1 ASP, 10 TL : 2 ASP, 10 TL : 3 ASP, 10 TL : 4 ASP, 10 TL : 5 ASP. Dusty of Chaff Paddy to be used is beforehand sieved so that become refinement and clear of small stones and fibre so that/ to be easy to in course of and mixture printing of tile, is later; then mixed with clay and processed with printing of tile result of from tile printing;mould dried until tile is ready to burned, hereinafter process combustion of rose colored tile until. refinement as according to specification in SNI 03-2095-1998. Examination relate at SNI 03-2095-1998 about visible quality, decision of size measure, form, limber strength and absorbtion. From is sixth of mixture composition indicate that energy diffuse dusty clay tile water of terendah paddy chaff at III mixture ( 10 TL : 2 ASP) equal to 6,28 % below/under SNI 03-2095-1998 equal to 15 % and enter in storey;level quality of II. Strong flex highest at III composition ( 10 TL : 2 ASP) equal to 169,95 Singk / cm enter in storey;level quality of II tile and limber strength of minimum at VI composition ( 10 TL : 5 ASP) equal to 133,67 Singk / cm ( SNI 03-2095-1998 min. 110 Singk / cm2